Plurality And Multiculturality In Islamic Religious Education Learning In Elementary School - Fahri Yahya Ainuri; Amelia Novianti; Iron Maulana; Radda Mutia Yahya (at-Tarbiyah al-Mustamirrah: Jurnal Pendidikan Islam, 2026)
This study aims to review relevant scientific articles related to pluralism and multiculturalism in Islamic Religious Education (PAI) at the elementary school level. The research method employed in this article is a literature review. The literature review is based on articles published within the last five years. The literature search was conducted using several keywords, such as "Pluralism and Multiculturalism in Islamic Religious Education Learning in Elementary Schools." Articles were sourced from Google Scholar. The analysis results indicate that, overall, these studies demonstrate that the implementation of multicultural PAI learning in elementary schools can enhance students' understanding, awareness, and attitudes of tolerance towards religious and cultural diversity. This underscores the importance of a multicultural approach in education to foster a more inclusive generation that values differences. By involving teachers, parents, and appropriate learning strategies, it is hoped that PAI learning can be more effective in creating a harmonious environment in schools. The conclusion of this study highlights the significance of differentiated learning in creating an inclusive learning environment that is responsive to the diverse learning styles and abilities of students. These findings provide a clear picture of the importance of multicultural education in the context of Islamic education and how various factors can influence its implementation in schools